Synthesis of Some Novel Proponohydrazides and Substituted Pyrazolones - Kumar Singh, Amrendra; Kumar Srivastava, Ashok; Singh, Daroga; Kumar Singh, Hemant; Kumar, Indresh (Asian Journal of Chemistry, 2010)
4-(4-Methoxybenzoyl)-5-(4-methoxyphenyl)-2,3-furandione (1) reacted with N-aryl substituted phenyl-hydrazones (3a-h) via the p,p'-dimethoxydibenzoylketene intermediate (2) giving the proponohydrazide derivatives (5a-h). In addition, compounds 5a-h were converted into corresponding pyrazolone derivatives (7i, j) by the reactions of hydrolysis in acidic solution. The structures of these compounds were determined by 13C NMR, 1H NMR and IR spectroscopic data and elemental analysis.